Economic Sociology - Vladimirov, Zhelyu (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The course Economic Sociology is designed for the undergraduate fourth-year students of the Faculty of Economics and Business Administration at Sofia University "St. Kliment Ohridski." During the previous years they are taught mainly classical economics (micro-, macro-), mathematics, and statistics, which intimate them with formal models of economic behavior. The Economic Sociology is offered in the 8th semester as an optional course (30 hours) with the aim to give students a larger societal perspective on economic phenomena. It will allow them to better understand the interdependence among economic, social, political and cultural factors and will diversify their employability. The course is justified by the fact that in the last 15 years East-European economies have been deeply transformed, and their well-functioning depends strongly on both economic and non-economic factors. Thus the social context is quite stimulating to the topics the course is dealing with (legal environment for economic development, social determinants of market behavior and entrepreneurship, networks firm, intra-firm coordination, informal economy, economic role of the State, national models of economic development, etc.).